Investigation of the Intervention Mechanism of Traditional Chinese Medicine in Knee Osteoarthritis Based on the Focal Cell Death Theory - Wang, Yaohui; Chen, Bing; Li, Hongfu; Yang, Yucheng; Cui, Zhuo (Journal of Contemporary Medical Practice, 2024)
Knee osteoarthritis (KOA) is a common orthopaedic disease in middle-aged and elderly people, and its pathogenesis has not been fully understood. Cellular pyroptosis, a non-apoptotic programmed cell death, is widely implicated in the onset, development and progression of many diseases. TCM intervenes in the treatment of KOA by inhibiting the production of cellular pyrolysis to reduce osteoarthritis, chondrocyte death and synovial tissue lesions. In this paper, we will review the pathway of cellular pyroptosis, cellular pyroptosis-related factors mediating the development of KOA, and Chinese medicine intervention in KOA based on the theory of cellular pyroptosis according to the relevant studies at the domestic and international level, so as to provide new ideas for Chinese medicine intervention in the treatment of KOA.